2005
DOI: 10.1007/s00464-004-8823-z
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic cholecystectomy in cirrhotic patients

Abstract: Currently, the classification of cirrhotic patients is normally done using the CTP score. However, preoperative platelet levels and INR more accurately predict the difficulty of cholecystectomy than CTP score, because intraoperative hemorrhage is the primary concern in these patients. This study demonstrates that preoperative degree of coagulopathy, and not Child's class, should guide the surgeon's approach and expectations when LC is performed in a cirrhotic patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 11 publications
0
36
0
2
Order By: Relevance
“…For patients undergoing laparoscopic cholecystectomy, a preoperative MELD score of 8 was linked to high morbidity, and was suggested as the cutoff value for avoiding the operation in patients with liver cirrhosis [221] . However, Schiff et al [222] recently reported that preoperative platelet levels and PT (international normalized ratio) are more important factors for the safety of cholecystectomy than C-P grade.…”
Section: Risk Of Surgery In Patients With Liver Diseasesmentioning
confidence: 99%
“…For patients undergoing laparoscopic cholecystectomy, a preoperative MELD score of 8 was linked to high morbidity, and was suggested as the cutoff value for avoiding the operation in patients with liver cirrhosis [221] . However, Schiff et al [222] recently reported that preoperative platelet levels and PT (international normalized ratio) are more important factors for the safety of cholecystectomy than C-P grade.…”
Section: Risk Of Surgery In Patients With Liver Diseasesmentioning
confidence: 99%
“…Cholecystectomy and hernia repair surgery are the most frequently described surgeries in LC, and modified laparoscopic techniques have been proposed in these cases in order to minimize morbidity (Table 2) [77][78][79][80][81][82] . The use of laparoscopy allows non-exposure of viscera and restricts electrolytic and protein losses [79] .…”
Section: Surgical Considerationsmentioning
confidence: 99%
“…A wide range of interventions can be performed laparoscopically in LC patients: splenectomies, colectomies, Nissen fundoplication, Heller's myotomy, gastric bypass, radical nephrectomy [88] , appendectomies [89] , suture closure, and placement of an omental patch for treatment of a perforated gastric ulcer [90] . Although, in general, outcomes are poorer in LC patients than in the non-LC population in terms of morbidity and mortality, mortality rates are quite similar in certain surgeries thanks to the technical advances and experience gained in recent years (Table 3) [10,[77][78][79][81][82][83][84][85][86][87]89,[91][92][93][94][95][96][97][98][99][100][101] . One example is abdominal wall surgery.…”
Section: Surgical Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with severe liver dysfunction who have to undergo cholecystectomy, laparoscopic cholecystectomy, partial hepatic resection, or other medium or major surgical interventions, there is an association between PT and postoperative bleeding [2,21,43,65]. The purpose of plasma therapy is to raise PT levels to more than 50% [43].…”
Section: Liver Damagementioning
confidence: 99%